Morphological Errors Made by Secondary School Learners and their Effect on Writing in Kenya - Kabellow , Joseph K.; Rwito , Doris Nthiori; Matere , Audrey (African Journal of Education,Science and Technology (AJEST), 2015)
This paper examines the morphological errors made by students in secondary schools and how these errors affect the quality of learners‘writing. Theseare the underlying issues that emerged out of a research conducted in Migwani Sub-county of Kitui County, 2012-2013. The study was based on Ellis (1994) Error Analysis Model, which outlines four major steps in error analysis namely: selection of corpus identifying errors, classifying errors and explanation of the different types of errors. The study focused in form one learner‘s in secondary schools. It employed purposive, stratified and random sampling techniques. Teacher questionnaire and learners‘ essays were used to collect data. The data collected was analyzed qualitatively and quantitatively through the use of numbers, descriptive statistics and presented in frequency tables and percentages.The study revealed that morphological errors affect learners‘ quality writing; most learners used the present tense where the past tense should have been used, they also attached the past tense marker to an infinite, they also had affixation and prefixation errors and finally wrong plural formation errors. The study recommends: Teachers should pay more attention to writing to help learners to develop skills in producing standard language. This can be done by giving more frequent writing assignments at least once a month. Teachers of English need also to carefully go through the KIE English syllabus and the KNEC essay marking scheme. This will make them realise how seriously morphological errors are taken and allow them to guide their learners from an informed position.